1995
DOI: 10.1111/j.1530-0277.1995.tb01516.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Cytochrome P4502E1 as Assessed by the Rate of Chlorzoxazone Hydroxylation in Alcoholics during the Withdrawal Phase

Abstract: To evaluate cytochrome P4502E1 (CYP2E1) induction in alcoholics, the ratio of the concentrations of 6-hydroxychlorzoxazone (6-OH-CHZ) and chlorzoxazone (CHZ) was measured in blood 2 hr after CHZ ingestion using a HPLC method. This ratio was determined in controls and in alcoholic patients after 1, 2, 3, 4, 5, 8, and 21 days withdrawal. It was found to be 0.34 +/- 0.03 in 30 controls and 1.05 +/- 0.14 in 41 alcoholic patients within 2 days following ethanol withdrawal. This ratio decreased rapidly during withdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 22 publications
1
36
1
Order By: Relevance
“…Studies in humans demonstrate that induction of CYP2E1 by alcohol is transient, lasting only a few days following cessation of alcohol exposure. 10 As the development of hepatic injury is determined by the production of NAPQI and the GSH concentration, the period of highest risk for alcohol abusers is expected immediately after discontinuation of alcohol intake (newly abstinent abusers). At this time, the production of NAPQI is the highest and the concentration of GSH is decreased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in humans demonstrate that induction of CYP2E1 by alcohol is transient, lasting only a few days following cessation of alcohol exposure. 10 As the development of hepatic injury is determined by the production of NAPQI and the GSH concentration, the period of highest risk for alcohol abusers is expected immediately after discontinuation of alcohol intake (newly abstinent abusers). At this time, the production of NAPQI is the highest and the concentration of GSH is decreased.…”
Section: Resultsmentioning
confidence: 99%
“…We administered the maximum approved dose of paracetamol to alcohol-abusing subjects for five consecutive days. Our subjects received paracetamol in a period of CYP2E1 induction and reduced plasma glutathione concentration, [8][9][10][11] thereby creating the conditions postulated to allow liver injury in patients who abuse alcohol. The results indicate that administration of paracetamol 4 g per day for 5 days to newly abstinent alcohol-abusing subjects was followed by a small increase in the serum ALT.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the enhanced capacity to metabolize alcohol is not retained indefinitely, and after a period of abstinence, the elimination rate of ethanol returns to values expected for moderate drinking, namely, 0.15 g l −1 h −1 [30]. In-vitro studies demonstrate a rapid turnover in the microsomal CYP2E1 enzyme after the absence of substrate [10,41].…”
Section: Discussionmentioning
confidence: 99%
“…The CYP2E1 activities decreased after cessation of intoxication down to control values within 24 hr in one study (Lucas et al, 1995b), whereas it was still abnormal after 8 days in another study that used a higher dose of CZX (Mishin et al, 1998). In any event, it was found that measurement of plasma 6-OH-CZX after administration of a CZX challenge can serve as a marker of hepatic CYP2El activity.…”
Section: Diagnostic Testsmentioning
confidence: 97%